Potential Patient-Reported Toxicities With Disulfiram Treatment in Late Disseminated Lyme Disease - Trautmann, Alain; Gascan, Hugues; Ghozzi, Raouf (Frontiers in Medicine, 2020)
Recently, disulfiram has been proposed as a promising treatment for people suffering from persistent symptoms of Lyme disease. Disulfiram has several distinct molecular targets. The most well known is alcohol dehydrogenase, a key enzyme for detoxifying the organism after alcohol ingestion. Other targets and modes of action of disulfiram, that may present problematic side effects, are less commonly mentioned. The French Federation against Tick Borne Diseases (French acronym, FFMVT), gathering three main Lyme patient organizations, MDs and PhDs, has recently been alerted to severe and persistent toxic events in a patient suffering from a late disseminated form of Lyme disease following disulfiram intake. Patient organizations reacted by launching a national call to know whether other patients in France following a similar treatment could be identified, and what benefits, or side effects could be reported. The statements of 16 patients taking disulfiram have been collected and are presented here. 13 out of 16 patients self-reported toxic events, and 7 out of 16 reported benefits for at least part of their symptoms. Based on the collected observations, it seems too early to promote disulfiram as a promising new treatment, before the reasons underlying such toxicities have been seriously explored, and the result of a well-conducted double blind clinical trial published. The importance of taking into account patient-reported outcomes in Lyme disease is underlined by the present study.